Development of an Identification Instrument for Dyscalculia in Early Childhood (Ages 4-6): A Dichotomous Model Three Parameters Logistic Approach in Item Response Theory - Kusumah, Indra Praja; Wardhani, M. Kusuma (JURNAL PENDIDIKAN DASAR NUSANTARA, 2025)
This study aims to develop and validate an identification instrument for dyscalculia in early childhood (ages 4-6) using the Dichotomous Model Three Parameters Logistic approach within Item Response Theory (IRT). The research was conducted in two stages. The first stage involved determining dyscalculia indicators in early childhood through a literature review and focus group discussions (FGD) with special education experts. The outcome of this stage was the identification of specific indicators that served as the foundation for developing the instrument's blueprint. The second stage focused on the development and validation of the instrument, which consisted of dichotomous question items in accordance with the chosen IRT model. The instrument validation was carried out by involving experts in early childhood education and special education. The research results showed that the developed instrument has good content validity and can be used as a tool to identify dyscalculia in early childhood. This instrument is expected to assist educators and psychologists in the early detection of children with dyscalculia, enabling earlier intervention.